2019
DOI: 10.1177/1748302619845783
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte nucleus segmentation method based on enhancing the saliency of saturation component

Abstract: The accuracy of the leukocyte nucleus segmentation is an important preprocessing step in the leukocyte automatic analysis. However, different dyeing conditions or different illumination conditions may cause capturing different color leukocyte images in microscopic imaging system, which will result in the over-segmentation or under-segmentation of the leukocyte nucleus. A leukocyte nucleus segmentation method based on enhancing the saliency of the saturation component is proposed. While applying the set of cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Color images are segmented more easily than grayscale images as it is more accurate since there is more information at the pixel level. [ 23 ]. Images in the dataset are translated to the following color spaces: HSV: The HSV color space is represented in three dimensions by a hexacone where intensity is represented by a central vertical axis [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Color images are segmented more easily than grayscale images as it is more accurate since there is more information at the pixel level. [ 23 ]. Images in the dataset are translated to the following color spaces: HSV: The HSV color space is represented in three dimensions by a hexacone where intensity is represented by a central vertical axis [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bogert et al [15] believe that it needs to transform the original image, the calculation is more complex, and the amount of data is large, but the digital boundary judgment algorithm in the transform domain can resist the influence of compression coding and low-pass filtering; it can effectively resist such as JPEG compression; the energy distribution in the transform domain is concentrated and easily combined with the human visual system (HVS) to determine the strength of embedded digital media. Wang and Cao [16] found that the method of embedding digital media based on transform domain has many advantages over the method of embedding digital media based on spatial domain, so it is very suitable for application in digital digital media technology. Vazquez and Bertalmío [17] proposed a digital boundary judgment algorithm based on the boundary judgment tree of important coefficients, which uses the boundary judgment of zero-tree coding and the masking of the human visual system to judge the boundary of the blue component (the least sensitive of the human eye) of the color image.…”
Section: Related Workmentioning
confidence: 99%
“…Color images are segmented more easily than grayscale images as it is more accurate since there is more information at the pixel level. [23]. Images in the dataset are translated to the following color spaces:…”
Section: Color Conversion From Rgb To Hsv Hls and Ycbcr Color Spacementioning
confidence: 99%